Por uma leitura filológica dos causos sertanejos de Eulálio Motta nas aulas de língua portuguesa: plataforma digital Bahia Humorística na escola - Almeida, Elizabeth Mota Nazareth de (2022)
This thesis, entitled For a philological reading of causos sertanejos of Eulálio Motta in Portuguese language classes: Bahia Humorous Digital Platform at school, inserted in scope of Postgraduate Program in Linguistic Studies (PPGEL), of Universidade Estadual de Feira de Santana (UEFS), aims to present the edition of causos sertanejos by Eulálio de Miranda Motta, through a digital platform, aimed at reading in high school classes, in Basic Education. As a corpus for this research, 50 causos sertanejos present in Bahia Humorística notebook (BARREIROS, 2012; 2016) were used, as well as prototextual and paratextual documents related to the texts. For this, researcher developed, especially for this research, platform Bahia Humorística na Escola: Plataforma Digital dos sertanejos de Eulálio Motta, which is available at https://www.bahiahumoristicanaescola.com/ or at alternative address https://bahiahumoristica.wixsite.com/naescola2. The construction of platform was based mainly on principles and guidelines for editions in digital media proposed by authors such as Shillingsburg (1993; 1996; 2010) and Sahle (2016), in addition to recommendations proposed by Barreiros (2013; 2015; 2018). Regarding methodology, this thesis is inserted in the scope of digital philology, the sociology of texts and textual criticism applied to pedagogical practice. Through the Bahia Humorística na Escola digital platform, causos sertanejos of Eulálio Motta were presented from editorial layers, such as facsimile editing, topographical editing, linearized editing (with adaptation of genetic apparatus in interactive explanatory captions) and updated editions, printed, digital and with the glossary integrated into the text. The bibliographic and contextual elements related to texts are accessed in a hypertextual way through hypermedia resources. From the causos, didactic resources were elaborated, printed and digital, with a view to discussing the inclusion of non-canonical writers in Portuguese Language classrooms, raising debates about linguistic and identity issues focused on variation of popular Portuguese, as well as how to contribute to reading formation and development of philological competences of teachers and students inserted in a digital technological society. Thus, from this thesis work, a possible way is presented to combine philological praxis with educational purposes, through digital technological resources, in view of use of materials from collection of writers who underwent philological treatment in Portuguese language classrooms.